MANAJEMEN KURIKULUM BAHASA ARAB JENJANG SEKOLAH DASAR / MADRASAH IBTIDAIYAH DI INDONESIA - Zhafir Al Hazmi, Muhammad; Nurzahira, Fadhilah (As-Sulthan Journal of Education, 2025)
This study discusses Arabic language curriculum management at the elementary school and madrasah ibtidaiyah (SD/MI) levels in Indonesia, emphasizing the four main functions of educational management: planning, organizing, implementing, and evaluating. This study uses a descriptive qualitative approach based on the analysis of policy documents such as KMA Number 183 and 184 of 2019, SK Dirjen Pendis Number 3302 of 2024, and Permendikbudristek Number 5 and 21 of 2022. The results of the study show that the implementation of the Arabic language curriculum is influenced by internal factors such as teacher competence, institutional support, and availability of facilities, as well as external factors such as government policy, technological developments, and community support. The roles of teachers, school principals, and the government are key to the success of effective, adaptive, and sustainable curriculum management. The main obstacles faced include limited teacher competence, learning facilities, and low student interest in learning Arabic. Therefore, strengthening teacher training, digitizing learning, and cross-institutional collaboration are necessary to realize communicative, contextual Arabic learning that is relevant to the needs of the times.